Multimodal evaluation of 19F-BPA internalization in pancreatic cancer cells for boron capture and proton therapy potential applications. (February 2022) - Ciardiello, Andrea; Altieri, Saverio; Ballarini, Francesca; Bocci, Valerio; Bortolussi, Silva; Cansolino, Laura; Carlotti, Daniele; Ciocca, Mario; Faccini, Riccardo; Facoetti, Angelica; Ferrari, Cinzia; Ficcadenti, Luca; et al.
Highlights: 19 F-BPA is significantly internalized in PANC-1 cells. At 120 ppm of 11 B 19 F-BPA has an internalization ratio equal to 0.5. 19 F-MRS can detect and quantify the therapeutic 19 F-BPA doses useful in BNCT/PBFT. 19 F-BPA is a promising BNCT/PBFT carrier and tracer for the treatment of pancreatic cancer. Abstract: Purpose: One of the obstacles to the application of Boron Neutron Capture Therapy (BNCT) and Proton Boron Fusion Therapy (PBFT) concerns the measurement of borated carriers' biodistribution. The objective of the present study was to evaluate the in vitro internalization of the 19 F-labelled p -boronophenylalanine ( 19 F-BPA) in the human cancer pancreatic cell line (PANC-1) for the potential application of BNCT and PBFT in pancreatic cancer. The 19 F-BPA carrier has the advantage that its bio-distribution may be monitored in vivo using 19 F-Nuclear Magnetic Resonance ( 19 F NMR). Materials and methods: The 19 F-BPA internalization in PANC-1 cells was evaluated using three independent techniques on cellular samples left in contact with growing medium enriched with 13.6 mM 19 F-BPA corresponding to a 11 B concentration of 120 ppm: neutron autoradiography, which quantifies boron; liquid chromatography hyphenated to tandem mass spectrometry and UV-Diode Array Detection (UV-DAD), which quantifies 19 F-BPA molecule; and 19 F NMR spectroscopy, which detects fluorine nuclei. Results: Our studies suggested that 19 F-BPA is internalized by PANC-1 cells. The three methods provided consistent results of about 50% internalization fraction at 120 ppm of 11 B. Small variations (less than 15%) in internalization fraction are mainly dependent on the proliferation state of the cells. Conclusions: The ability of 19 F NMR spectroscopy to study 19 F-BPA internalization was validated by well-established independent techniques. The multimodal approach we used suggests 19 F-BPA as a promising BNCT/PBFT carrier for the treatment of pancreatic cancer. Since the quantification is performed at doses useful for BNCT/PBFT, 19 F NMR can be envisaged to monitor 19 F-BPA bio-distribution during the therapy.